2021
DOI: 10.32604/csse.2021.017191
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Automatic Detection Using Deep Learning

Abstract: The novel coronavirus disease 2019 (COVID-19) is a pandemic disease that is currently affecting over 200 countries around the world and impacting billions of people. The first step to mitigate and control its spread is to identify and isolate the infected people. But, because of the lack of reverse transcription polymerase chain reaction (RT-CPR) tests, it is important to discover suspected COV-ID-19 cases as early as possible, such as by scan analysis and chest X-ray by radiologists. However, chest X-ray anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The majority of the studies used GANs to augment the data, where they reported the use of GANs to increase the data set size. Specifically, 42 (74%) studies used GAN-based methods for data augmentation [ 18 , 21 , 23 - 29 , 31 - 36 , 38 - 43 , 45 , 46 , 48 , 50 , 52 - 56 , 59 - 67 , 71 , 73 , 74 ]. The augmented data were then used to improve the training of different CNNs to diagnose COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies used GANs to augment the data, where they reported the use of GANs to increase the data set size. Specifically, 42 (74%) studies used GAN-based methods for data augmentation [ 18 , 21 , 23 - 29 , 31 - 36 , 38 - 43 , 45 , 46 , 48 , 50 , 52 - 56 , 59 - 67 , 71 , 73 , 74 ]. The augmented data were then used to improve the training of different CNNs to diagnose COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the use of X-ray images dominated the studies. In total, 29 (51%) studies used X-ray images of lungs [ 20 , 21 , 25 , 27 - 29 , 31 , 32 , 35 , 37 , 40 - 43 , 45 , 50 , 52 , 54 , 56 , 57 , 59 , 60 , 62 , 64 , 65 , 67 , 70 , 73 , 74 ], while 21 (37%) studies used CT images [ 18 , 19 , 22 - 24 , 26 , 30 , 33 , 34 , 36 , 38 , 48 , 49 , 51 , 53 , 55 , 58 , 61 , 63 , 66 , 71 ], and 6 (11%) studies reported the use of both X-ray and CT images [ 39 , 44 , 46 , 47 , 68 , 72 ]. Only 1 (2%) study used ultrasound images for COVID-19 diagnosis [ 69 ], which shows that ultrasound is not a popular imaging modality for training GANs and other deep learning models for COVID-19 detection (also see Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our model can quickly detect wear or not wearing a mask by producing a higher accuracy with tiny loss. Based on the experimental result, the proposed model can be a promising solution to deal with face mask detection issues using the real and huge dataset [19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The equations utilized to assess the performance of feature selection are illustrated in Table 5. The symbols used in the equations are as follows: TP represents the count of true positives, FN represents the count of false negatives, TN represents the count of true negatives, and FP represents the count of false positives [50], [51], [52], [53], [54], [55].…”
Section: A Evaluation Metricsmentioning
confidence: 99%